Resisting by Obeying: the Legitimation of Indigenous Authorities through Parish Elections of the Bishopric of Puebla, 1789-1835 - Gómez García, Lidia E. (Anuario de Historia de América Latina, 2025)
The resistance to the electoral reforms of the Constitutional City Councils, by the República de Naturales, marked the political practice that, with the establishment of the nation-state, modified the symbols of legitimacy of the new authorities and outlined an alternative way of participating in their government through the emerging concept of citizenship. They did so by constantly interpreting and adapting the new system to the traditional corporate regime. The mechanism was the legitimizing reference: the parish, a symbol of identity and recognition, which allowed the indigenous authorities to maintain their collection capacity.